An Ancestral Retrovirus Envelope Protein Regulates Persistent Gammaherpesvirus Lifecycles - Frey, Tiffany R.; Akinyemi, Ibukun A.; Burton, Eric M.; Bhaduri-McIntosh, Sumita; McIntosh, Michael T. (Frontiers in Microbiology, 2021)
Human gammaherpesviruses Epstein-Barr virus (EBV) and Kaposi’s sarcoma-associated herpesvirus (KSHV) persist as life-long infections alternating between latency and lytic replication. Human endogenous retroviruses (HERVs), via integration into the host genome, also represent persistent infections. Both show similar epigenetic silencing while dormant, but can reactivate in response to cell signaling cues or triggers that, for gammaherpesviruses, result in productive lytic replication. Given their coevolution with humans and shared epigenetic silencing, we asked if HERV expression might be linked to lytic activation of gammaherpesviruses. We found ERVW-1 mRNA, encoding the functional HERV-W envelope protein Syncytin-1, along with other repeat class elements, to be elevated upon lytic activation of EBV. Knockdown/knockout of ERVW-1 reduced lytic activation of EBV and KSHV in response to various lytic cycle triggers. In this regard, reduced expression of immediate early proteins ZEBRA and RTA for EBV and KSHV, respectively, places Syncytin-1’s influence on lytic activation mechanistically upstream of the latent-to-lytic switch. Conversely, overexpression of Syncytin-1 enhanced lytic activation of EBV and KSHV in response to lytic triggers, though this was not sufficient to induce lytic activation in the absence of such triggers. Syncytin-1 is expressed in replicating B cell blasts and lymphoma-derived B cell lines where it appears to contribute to cell cycle progression. Together, gammaherpesviruses and B cells appear to have coevolved a dependency on Syncytin-1 that facilitates the ability of EBV and KSHV to activate lytic replication from latency, while promoting viral persistence during latency by contributing to B cell proliferation.